2010
DOI: 10.1109/tasl.2010.2052252
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Source Separation Algorithms With Reverberant Speech

Abstract: Abstract-This paper examines the performance of several source separation systems on a speech separation task for which human intelligibility has previously been measured. For anechoic mixtures, automatic speech recognition (ASR) performance on the separated signals is quite similar to human performance. In reverberation, however, while signal separation has some benefit for ASR, the results are still far below those of human listeners facing the same task. Performing this same experiment with a number of orac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Stereo to multichannel upmix [38] is also a vibrant area of research to which advanced source separation systems could contribute and for which novel performance criteria are needed. Appropriate statistical confidence measures, tighter oracle performance bounds and advanced diagnosis procedures such as those in [39,40,41] are also needed to increase the insight that can be gained from evaluation. Finally, increased publicity and networking efforts should be made to promote source separation evaluations in the biomedical signal processing community, as well as in other communities, e.g.…”
Section: Evaluation Methodologymentioning
confidence: 99%
“…Stereo to multichannel upmix [38] is also a vibrant area of research to which advanced source separation systems could contribute and for which novel performance criteria are needed. Appropriate statistical confidence measures, tighter oracle performance bounds and advanced diagnosis procedures such as those in [39,40,41] are also needed to increase the insight that can be gained from evaluation. Finally, increased publicity and networking efforts should be made to promote source separation evaluations in the biomedical signal processing community, as well as in other communities, e.g.…”
Section: Evaluation Methodologymentioning
confidence: 99%
“…The PESQ score is computed by a comparison of the original (unmixed, anechoic) speech source signal to the recovered signal estimate. Both signals are time-aligned and passed through an auditory transform to achieve a psychoacoustically motivated representation [55]. The differences between the signals in this representation are measured and used to provide an estimate of the distortion in the signal estimate.…”
Section: Pesqmentioning
confidence: 99%
“…A recent study [5] has suggested a metric for assessing the separation of reverberated speech. The metric, termed direct-path, early echoes, and reverberation of target and masker (DERTM), measures the suppression of the direct sound, early reflections and late reverberation of both the target and interfering sounds.…”
Section: Ideal Binary Masks and Metricsmentioning
confidence: 99%